Does the Upstream Region Possessing MULE-Like Sequence in Rice Upregulate PsbS1 Gene Expression? - Nuruzzaman, Mohammed (Public Library of Science, 2014)
The genomic nucleotide sequences of japonica rice (Sasanishiki and Nipponbare) contained about 2.7-kb unique region at the point of 0.4-kb upstream of the OsPsbS1 gene. In this study, we found that japonica rice with a few exceptions possessing such DNA sequences [denoted to OsMULE-japonica specific sequence (JSS)] is distinct by the presence of Mutator-like-element (MULE). Such sequence was absent in most of indica cultivars and Oryza glaberrima. In OsMULE-JSS1, we noted the presence of possible target site duplication (TSD; CTTTTCCAG) and about 80-bp terminal inverted repeat (TIR) near TSD. We also found the enhancement ofOsPsbS1 mRNA accumulation by intensified light, which was not associated with the DNA methylation status in OsMULE/JSS. In addition, O. rufipogon, possible ancestor of modern rice cultivars was found to compose PsbS gene of either japonica (minor) or indica (major) type. Transient gene expression assay showed that the japonica type promoter elevated a reporter gene activity than indica type.